2012
DOI: 10.1111/j.1360-0443.2011.03750.x
|View full text |Cite
|
Sign up to set email alerts
|

Abstinence‐contingent recovery housing and reinforcement‐based treatment following opioid detoxification

Abstract: Aims To conduct a randomized, controlled trial of abstinence-contingent recovery housing delivered with or without intensive day treatment among individuals exiting residential opioid detoxification. Design Random assignment to one of three conditions: Recovery housing alone (RH), abstinence-contingent recovery housing with RBT (RH+RBT), or usual care (UC). RH and RH+RBT participants received 12 weeks of paid recovery housing contingent upon drug abstinence. RH+RBT participants also received 26 weeks of RBT,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 29 publications
1
32
0
1
Order By: Relevance
“…No meta-analyses or research reviews on recovery housing were found. We identified five articles describing RCTs that compared some version of recovery housing to some control condition (4,(11)(12)(13)(14) and one quasi-experimental study with a within-group, repeatedmeasures design (15). However, four of the five articles describing RCTs reported on the same base study; therefore, only three distinct studies on this topic met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…No meta-analyses or research reviews on recovery housing were found. We identified five articles describing RCTs that compared some version of recovery housing to some control condition (4,(11)(12)(13)(14) and one quasi-experimental study with a within-group, repeatedmeasures design (15). However, four of the five articles describing RCTs reported on the same base study; therefore, only three distinct studies on this topic met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 98%
“…Two studies indicated that outcomes were better with longer stays in the recovery house (12,14). In addition, several studies indicated that success in the recovery house may also depend on other client characteristics, such as involvement in a 12-step program, age, or a diagnosis of posttraumatic stress disorder (11)(12)(13).…”
Section: Discussionmentioning
confidence: 97%
“…Moderate-quality evidence indicates that this approach, when administered without linkage to long-term addiction treatment and care, is associated with elevated risk of relapse, HIV and hepatitis C transmission, and death from drug overdose. [66][67][68] Patients should be clearly informed of the known risks of withdrawal management alone and engaged in discussion about other treatment options corresponding to their individual needs and circumstances.…”
Section: Offering Withdrawal Management Alone (Ie Detoxification Wmentioning
confidence: 99%
“…[38][39][40] These studies have demonstrated superior abstinence rates for clients receiving RBT for as long as six months following treatment. As noted, there also is preliminary evidence for the effectiveness of a home-based version of RBT delivered within MST-CAN.…”
Section: Empirical Support For Rbtmentioning
confidence: 99%